Pain, psychological distress and health-related quality of life at baseline and 3 months after radical prostatectomy - Johansson Fannie; Nordberg Gunnar; Ene Kerstin; Sjöström Björn (BMC, 2006)
Abstract Background Inadequate management of postoperative pain is common, and postoperative pain is a risk factor for prolonged pain. In addition to medical and technical factors, psychological factors may also influence the experience of postoperative pain. Methods Pain was measured postoperatively at 24, 48, and 72 hr in hospital and after 3 months at home in 140 patients undergoing radical prostatectomy (RP). Patients answered questionnaires about anxiety and depression (HAD scale) and health-related quality of life (SF-36) at baseline and 3 months after surgery. Results In the first 3 postoperative days, mild pain was reported by 45 patients (32%), moderate pain by 64 (45%), and severe pain by 31 (22%) on one or more days. High postoperative pain scores were correlated with length of hospital stay and with high pain scores at home. Forty patients (29%) reported moderate (n = 35) or severe (n = 5) pain after discharge from hospital. Patients who experienced anxiety and depression preoperatively had higher postoperative pain scores and remained anxious and depressed 3 months after surgery. The scores for the physical domains in the SF-36 were decreased, while the mental health scores were increased at 3 months. Anxiety and depression were negatively correlated with all domains of the SF-36. Conclusion There is a need for nurses to be aware of the psychological status of RP patients and its impact upon patients' experience of postoperative pain and recovery. The ability to identify patients with psychological distress and to target interventions is an important goal for future research.